2021
DOI: 10.1021/acs.jpcb.0c11152
|View full text |Cite
|
Sign up to set email alerts
|

Structural Flexibility of Cyclosporine A Is Mediated by Amide CisTrans Isomerization and the Chameleonic Roles of Calcium

Abstract: Falling outside of Lipinski’s rule of five, macrocyclic drugs have accessed unique binding sites of their target receptors unreachable by traditional small molecules. Cyclosporin­(e) A (CycA), an extensively studied macrocyclic natural product, is an immunosuppressant with undesirable side effects such as electrolytic imbalances. In this work, a comprehensive view on the conformational landscape of CycA, its interactions with Ca2+, and host–guest interactions with cyclophilin A (CypA) is reported through exhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 82 publications
4
42
0
Order By: Relevance
“…Recently, Gray et al proposed the compact bent-twisted conformation of CsA via the results of the collision cross section (CCS) employing the distance geometry conformational sampling. 11 They confirmed that a minimum of two cis isomers (3−4 cis and 9−10 cis) existed in the conformation. This conformation corresponds to the position at (PC-1, PC-2) = (0.5, 0.45), where only AMBER12:EHT exhibited PMF ≈ 1.7 kcal/mol and the other force fields have PMF > 2.5 kcal/ mol using our bulk solvent simulations (Figure 2a and Figure S3), which is completely different from the one we found at (PC-1, PC-2) = (1.4, 0.0) that contains the same two cis isomers.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Recently, Gray et al proposed the compact bent-twisted conformation of CsA via the results of the collision cross section (CCS) employing the distance geometry conformational sampling. 11 They confirmed that a minimum of two cis isomers (3−4 cis and 9−10 cis) existed in the conformation. This conformation corresponds to the position at (PC-1, PC-2) = (0.5, 0.45), where only AMBER12:EHT exhibited PMF ≈ 1.7 kcal/mol and the other force fields have PMF > 2.5 kcal/ mol using our bulk solvent simulations (Figure 2a and Figure S3), which is completely different from the one we found at (PC-1, PC-2) = (1.4, 0.0) that contains the same two cis isomers.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…Expectedly, the canonical amino acids (Abu 2 , Val 5 , Ala 7 , and Dal 8 ) formed only trans isomers. Regarding the N-methyl amino acids, Mva 11 formed only a trans isomer, whereas the other N-methylated amino acids formed the cis and trans isomers.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 3 more Smart Citations